Pengaruh Penggunaan Metode Pembelajaran Project Based Learning (PjBL) terhadap Keterampilan Menulis Teks Ulasan Peserta Didik Kelas VIII di MTs. Nurul Bahri Kabila Bone Tahun Pelajaran 2024/2025: Penelitian - Endris, Indrawati; Supriyadi; Rachmi Masie, Sitti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the writing skills of review texts before and after the implementation of the Project Based Learning (PjBL) method in class VIII students of MTs Nurul Bahri Kabila Bone in the 2024/2025 academic year, as well as identify obstacles that arise during its implementation. The research method uses an experiment with a one-group pre-test and post-test design. Data were obtained through pre-tests and post-tests, then analyzed using a t-test with the help of the SPSS version 27 application, resulting in a significance value of 0.005. The results showed that the average score of students before the implementation of PjBL was 52.5 and increased to 89.9 after the implementation. The calculated t value of 0.001 is smaller than the t table of 0.005, which means there is a significant effect of the PjBL method on writing skills of review texts. However, the questionnaire results showed that 76.4% of students still had difficulty in formulating arguments critically. Therefore, further assistance and strategy adjustments are needed so that learning is more optimal and sustainable.